Multiple fusiform and saccular aneurysms in a person living with Human Immunodeficiency Virus - Talia Unice; Poobalan Naidoo; Pranav Hiralal; Yeshkhir Naidoo; Somasundram Pillay (SAGE Open Medical Case Reports)
Cerebral aneurysms secondary to human immunodeficiency virus vasculopathy are a diagnosis by exclusion and its mechanism is unknown. We report on a 21-year-old male with human immunodeficiency virus infection and suboptimal virological control, despite highly active antiretroviral therapy. An incidental discovery of multiple cerebral aneurysms occurred in this patient, who initially presented with signs of disorientation, acute psychosis, and a history of blunt cranial trauma. A non-contrasted computerized tomography scan of the encephalon showed no intracranial hemorrhage but multiple cerebral (saccular and fusiform) aneurysms. Subsequently, a non-urgent computerized tomography angiogram of the cerebral vasculature corroborated the existence of multiple cerebral aneurysms. Despite investigation, no secondary etiological factors for the aneurysmal condition were identified. The multitude of cerebral aneurysms was consequently ascribed to human immunodeficiency virus-associated vasculopathy. The patient was managed conservatively. At discharge, he was lucid and apsychotic. A unique aspect of the case is the presence of both fusiform and saccular cerebral aneurysms.